Penilaian Estetika Motif Betawi Sebagai Identitas Duta Fakultas Teknik Universitas Negeri Jakarta: Estetika Motif Betawi - Listiani Sri; Zahra E Lutfia (Pusat Penerbitan LPPM ISI Bali, 2026)
This study aimed to obtain an aesthetic evaluation of Betawi motifs designed as the visual identity of the Faculty of Engineering Ambassador at Jakarta State University. The motifs were developed as visual representations that reflect both Betawi cultural values and the institution's character. The research employed a descriptive quantitative method with a pre-experimental design using a one-shot case study approach. Data were collected through a questionnaire instrument administered to four expert panelists to assess the aesthetic quality of the motifs. The research variable consisted of the aesthetic evaluation of Betawi motifs based on three main indicators: form/appearance, content/substance, and presentation/display. The assessment was conducted using a rating scale to determine the aesthetic feasibility of each developed motif. The results showed that the content/substance aspect, which referred to the Indonesia Trend Forecasting 2023/2024 concept, achieved an excellent category with a score of 88%. The presentation/display aspect, including the sub-indicators of harmony, proportion, and rhythm, obtained a score of 87%, while the form/appearance aspect, consisting of the sub-indicators of shape, size, and color, achieved a score of 86.6%. Overall, the five evaluated Betawi motifs demonstrated good aesthetic quality and were considered suitable for use as the visual identity of the Faculty of Engineering Ambassador at Jakarta State University. Based on the panelists’ evaluation, the second motif obtained the highest score of 90.9%. This result was supported by the clarity of the motif design, which integrated ecoprint, shibori, and stamping techniques, a harmonious visual composition, an appropriate color combination aligned with the proposed theme, balanced proportions, and an appealing visual rhythm. Therefore, the second motif is recommended as the most suitable alternative for representing the visual identity of the Faculty of Engineering Ambassador at Jakarta State University.